Anomalous pulmonary fissural anatomy of the right lung- A case report - Arora J; Kumar A; Kumar Ravi Satish; Mehta V; Suri RK; Rath G (Department of Surgery, UKM Medical Centre, 2011)
Anatomical knowledge of variations of lobes of lung is important for accurately identification of broncho-pulmonary segments. It is of great significance for radiologists during interpretation of X-ray and CT scans. Such studies are of utmost importance during lobectomies and surgical resection of individual segments of lung. The present paper highlights the abnormal sinuous pattern of oblique fissure and incomplete horizontal fissure in right lung. It also describes in detail the morphology of an abnormal pyriform lobe present between these two fissures. We as anatomists wish to draw attention to abnormal morphological patterns of fissures of lungs which may be of utmost importance for radiologists and surgeons and add to the already existing knowledge of lobar anatomy